Characterization of [Ca2+]i responses in primary cultures of mouse cardiomyocytes induced by Trypanosoma cruzi trypomastigotes - Luciana R Garzoni; Masako Oya Masuda; Márcia M Capella; Anibal Gil Lopes; Maria de Nazareth S Leal de Meirelles (Memorias do Instituto Oswaldo Cruz, 2003)
Trypanosoma cruzi, the protozoan responsible for Chagas disease, employs distinct strategies to invade mammalian host cells. In the present work we investigated the participation of calcium ions on the invasion process using primary cultures of embryonic mice cardiomyocytes which exhibit spontaneous contraction in vitro. Using Fura 2-AM we found that T. cruzi was able to induce a sustained increase in basal intracellular Ca2+ level in heart muscle cells (HMC), the response being associated or not with Ca2+ transient peaks. Assays performed with both Y and CL strains indicated that the changes in intracellular Ca2+ started after parasites contacted with the cardiomyocytes and the evoked response was higher than the Ca2+ signal associated to the spontaneous contractions. The possible role of the extracellular and intracellular Ca2+ levels on T. cruzi invasion process was evaluated using the extracellular Ca2+ chelator EGTA alone or in association with the calcium ionophore A23187. Significant dose dependent inhibition of the invasion levels were found when intracellular calcium release was prevented by the association of EGTA +A23187 in calcium free medium. Dose response experiments indicated that EGTA 2.5 mM to 5 mM decreased the invasion level by 15.2 to 35.1% while A23187 (0.5 µM) alone did not induce significant effects (17%); treatment of the cultures with the protease inhibitor leupeptin did not affect the endocytic index, thus arguing against the involvement of leupeptin sensitive proteases in the invasion of HMC.